Analysis of Soft Soil Setting with Reinforcement Grouped Stone Column - Yudistira, I Gede Ngurah Arya; Lastiasih, Yudhi (Universitas Syiah Kuala, 2023)
The usage of stone columns in geotechnical practice is an common method for reinforcing soft soil. Soft soils often exhibit large consolidation behavior and low shear strength, requiring remedial action to support the structures above them. Stone columns are installed by embedding better materials into soft soil with the aim of increasing the bearing capacity and stability of the soil. This research examines the settlement behavior of soft soil reinforced with stone columns using finite element method analysis, with data from the finite element method analysis validated with field loading test data. From the results of the study, it is found that the behavior of stone columns in groups are different from single stone column. The behavior of grouped stone columns is strongly influenced by the area replacement ratio. When the ratio is large enough, the type of failure of the stone column tends to be shear failure, while the ratio is low, the reinforced behavior of the stone column tends to experience bulging failure. The settlement behavior of soft soil reinforced with stone columns is also greatly influenced by the area replacement ratio. It was found that the smaller the area replacement ratio, the greater the settlement that occurs.